Identifying factors that control medulloblastoma cell migration using a model of brain-CSF dissemination - Aldighieri, Macha (2020)
Introduction Medulloblastoma is the most common type of malignant paediatric brain tumour, accounting for 10% of cancer deaths in children. While survival rates have improved in recent years, metastatic spread poses a significant challenge to therapy success. Current therapies also cause irreparable damage to the surrounding brain leading to a decreased quality of life in surviving patients, consequently there is a need for new targeted therapy options. One of the routes for dissemination of metastatic cells is invasion into the leptomeninges, a process during which cells cross basement membrane barriers as they travel from the primary tumour niche into the metastatic niche in the cerebrospinal fluid (CSF). The pathways involved in dissemination and metastasis remain elusive, and a better understanding is crucial to developing targeted therapies. This project aimed to develop an in vitro model system to mimic key characteristics of cell migration from the brain to the CSF, and identify novel candidate genes driving medulloblastoma metastasis.